Stability of a surrogate African swine fever-like algal virus in corn- and soybean-based feed ingredients during extended storage and in vitro digestion processes - Shurson, Gerald C.; Ramirez-Camba, Christian D.; Urriola, Pedro E.; Schroeder, Declan C. (Frontiers in Veterinary Science, 2024)
Prevention of transmission of African swine fever virus (ASFV) through contaminated feed ingredients and complete feed is an important component of biosecurity protocols for global feed supply chains. Use of extended storage times for feed ingredients has become a popular and emerging mitigation strategy that may allow partial inactivation of ASFV before manufacturing swine feeds. However, the effectiveness of this strategy is unclear because limited studies have been conducted using diverse methodologies and insufficiently sensitive measures of virus viability of only a few types of feed matrices. Therefore, interpretation of results from these studies has made providing prudent recommendations difficult. Furthermore, although a few studies have shown that feed is a plausible route of transmission of ASFV to pigs, there are conflicting findings on the infectivity of ASFV that may be present in feed, which may be related to the extent that ASFV is degraded in the pig’s digestive system after it is consumed. Therefore, the objectives of this study were to use a surrogate ASFV-like algal virus (Emiliania huxleyi; EhV) to determine stability in corn- and soybean-based feed ingredients and complete feed during a 120-day storage period at temperatures up to 34°C, and EhV survival in various feed matrices during three stages of an in vitro digestion process. Results indicated that inoculating corn- and soybean-based feed ingredients and complete feed with EhV and storing them at 4°C, 24°C, or 34°C for up to 120 days did not result in the complete inactivation of EhV in any of these matrices. Because EhV has similar environmental and thermal resilience to ASFV, these results indicate that both viruses can maintain viability in various feed matrices during long-term storage and suggest that extending storage time up to 120 days is not an effective mitigation practice against ASFV. We also determined that between approximately 5- to more than 7-log (99.999 to 99.99999%) reductions in EhV in various feed matrices occur during the entire in vitro digestion and fermentation process. These reductions appear to be correlated with the chemical composition of the matrices, potentially explaining inconsistencies in ASFV infection when pigs consume infectious doses of contaminated feed.